Different FCER1A polymorphisms influence IgE levels in asthmatics and non‐asthmatics. Issue 5 (3rd June 2013) - Potaczek, Daniel P.; Michel, Sven; Sharma, Vishwas; Zeilinger, Sonja; Vogelberg, Christian; von Berg, Andrea; Bufe, Albrecht; Heinzmann, Andrea; Laub, Otto; Rietschel, Ernst; Simma, Burkhard; Frischer, Thomas; et al.
Abstract: Background: Recently, three genome‐wide association studies (GWAS) demonstrated FCER1A, the gene encoding a ligand‐binding subunit of the high‐affinity IgE receptor, to be a major susceptibility locus for serum IgE levels. The top association signal differed between the two studies from the general population and the one based on an asthma case–control design. In this study, we investigated whether different FCER1A polymorphisms are associated with total serum IgE in the general population and asthmatics specifically. Methods: Nineteen polymorphisms were studied in FCER1A based on a detailed literature search and a tagging approach. Polymorphisms were genotyped by the Illumina HumanHap300Chip (6 polymorphisms) or MALDI‐TOF MS (13 polymorphisms) in at least 1303 children (651 asthmatics) derived from the German International Study of Asthma and Allergies in Childhood II and Multicentre Asthma Genetics in Childhood Study. Results: Similar to two population‐based GWAS, the peak association with total serum IgE was observed for SNPs rs2511211, rs2427837, and rs2251746 (mean r 2 > 0.8), with the lowest p‐value of 4.37 × 10 −6 . The same 3 polymorphisms showed the strongest association in non‐asthmatics (lowest p = 0.0003). While these polymorphisms were also associated with total serum IgE in asthmatics (lowest p = 0.003), additional polymorphisms (rs3845625, rs7522607, and rs2427829) demonstrated associations with total serum IgE in asthmatics only (lowest p = 0.01). Conclusions: These data suggest that FCER1A polymorphisms not only drive IgE levels in the general population but that specific polymorphisms may also influence IgE in association with asthma, suggesting that disease‐specific mechanisms in IgE regulation exist.